Post-traumatic, intrapulmonary arteriovenous fi stula: Diagnosis by trans-oesophageal echocardiography - van der Bijl, Pieter; Herbst, Phillip G.; Doubell, Anton F.; Pecoraro, Alfonso J. (SA Heart Journal, 2017)
Image in Cardiology